1984
DOI: 10.1002/j.1460-2075.1984.tb01769.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and sequencing of the preprotoxin-coding region of the yeast M1 double-stranded RNA.

Abstract: Complementary DNA (cDNA) copies of the M1‐1, toxin‐coding region of the yeast M1 double‐stranded RNA (dsRNA) have been cloned and sequenced. These sequences, in combination with the known terminal sequence of M1‐1 dsRNA, identify a translation reading frame for a 316 amino acid protein of 34.7 kd, similar in size to the preprotoxin produced from M1 dsRNA by in vitro translation. Potential glycosylation sites in the preprotoxin peptide are identified. Based on its methionine content the extracellular yeast toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(33 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…2B). Hybridization of the labeled products of the M1-H and M1-L VLPs with M13 clones that contained M1 cDNA inserts in both orientations (27) (Table 3) showed that both peaks synthesize predominantly plus-strand (i.e., message strand) RNA. The phenolextracted RNA product is mainly single stranded as judged VOL.…”
Section: Methodsmentioning
confidence: 99%
“…2B). Hybridization of the labeled products of the M1-H and M1-L VLPs with M13 clones that contained M1 cDNA inserts in both orientations (27) (Table 3) showed that both peaks synthesize predominantly plus-strand (i.e., message strand) RNA. The phenolextracted RNA product is mainly single stranded as judged VOL.…”
Section: Methodsmentioning
confidence: 99%
“…1). A second, separately encapsidated viral dsRNA (M 1 ) encodes a secreted polypeptide toxin (k1 killer toxin) that provides a convenient phenotype for detecting synthesis of 34,37).Programmed, or directed, ribosomal frameshifting (PRF) is of particular value to viruses that package their plus strands, as it eliminates the need to splice their mRNAs and reduces the risk of packaging defective genomes. It also regulates the ratio of viral proteins synthesized.…”
mentioning
confidence: 99%
“…1). A second, separately encapsidated viral dsRNA (M 1 ) encodes a secreted polypeptide toxin (k1 killer toxin) that provides a convenient phenotype for detecting synthesis of Cap and Cap-Pol (4,34,37).…”
mentioning
confidence: 99%
“…In S. cerevisiae, the kl toxin consists of two subunits, alpha (103 amino acids) and beta (83 amino acids), joined by two disulfide bonds (5,42,54). These are encoded on one double-stranded RNA (dsRNA) of the S. cerev'isiae virus (ScV) and synthesized as a prepropolypeptide of 317 amino acids, which is cleaved by signal peptidase, the KEXi and KEX2 proteases, and by at least one more unspecified protease during its maturation (5,9,15,17,22,42,54 P6, respectively (24, 26-30). Their mode of action is unknown, but like the S. cerevisiae kl toxin, the KP6 toxin has cell wall receptors (44).…”
mentioning
confidence: 99%